G225(P) Communication Between Different Medical Specialities of Long Term Neuro-Rehabilitation Patients. (24th May 2017) - Scatchard, RE; Sharples, PM
Abstract : Objective: Neuro-rehabilitation in-patients are often complex long term cases with many specialist teams involved in their care. They require multiple referrals to other medical teams, and cohesive team work with clear communication to ensure that they receive timely assessments and treatment. We aimed to audit the clarity of case note documentation from the various involved specialities in the notes of neuro-rehabilitation patients who were inpatients December 2015 – January 2016. Methods: 10 concurrent medical notes were reviewed for information on dates of admission to neuro-rehabilitation, professionals involved (including whether there was a named lead consultant); ophthalmology, audiology, neuropsychology assessments and transfer between teams. We expected 100% compliance with all locally defined standards. Results: 8 of the 10 patients had other specialities additional to the neuro-rehabilitation team involved concurrently in their care. It was not clear from the notes when the patients were officially transferred to the neuro-rehabilitation team. Only 3/10 of the patients had a clearly named neuro-rehabilitation consultant. 9/ 10 patients required ophthalmology and audiology assessments, but it was not clear from the notes whether they had been referred; were awaiting an appointment, or had been seen and were waiting for the outcome of the review. Neuropsychology assessment was clearly documented in the notes in only 2 of the 8 cases referred for such an assessment. No patient had clear documentation of discharge planning meetings filed in the notes, nor an estimated date of discharge. Conclusion: This audit highlights significant weaknesses in case notes documentation for neuro-rehabilitation patients, which will potentially have a negative impact, not only on patient care and team efficiency, but also on the provision of discharge information. We are currently working on improved 'paperless' systems of communication, which will better capture essential information on these patients and contribute to the discharge summary and rehabilitation prescription.